Thin film deposition of NiO-YSZ composite cathode material for solid oxide electrolysis cell via screen-printing - Manalo, Agnes L.; Cervera, Rinlee Butch M. (Quezon City College of Engineering, University of the Philippines Diliman, 2019)
Cermet composites of nickel and yttria-stabilized zirconia (Ni-YSZ) are commonly used for solid oxide electrolysis cell cathodes because of their high electrochemical activity as well as their mixed ionic and electronic conductivity. In order to further study and enhance their electrical properties, cathode fabrication techniques are still continuously being developed in order to obtain desirable morphology and thickness. In this study, a porous thin film of NiO-YSZ was fabricated via screen-printing method. NiO-YSZ powder precursor was prepared using the glycine-nitrate process. A prepared precursor slurry was screen-printed onto a commercial YSZ substrate then sintered, and reduced to Ni-YSZ. The effect of precursor particle size reduction using planetary ball milling and of the use of PVP in the slurry as a binder on film uniformity and quality were investigated. Scanning electron microscope images of the film revealed a porous morphology and film thickness of around 5 microns, and that particle size reduction improved the adhesion and uniformity of the deposit. On the other hand, the use of binder in the slurry was also shown to improve the uniform deposition of the film. X-ray diffraction (XRD) patterns displayed distinct characteristics peaks that can be indexed to cubic NiO and YSZ, with calculated lattice parameters of 4.18 A and 5.14 A respectively. Electrochemical impedance spectroscopy (EIS) of the half-cell of NiO-YSZ film and YSZ substrate under O2 atmosphere revealed a total conductivity of about 4.2 mS/cm at 700°C. After reduction of NiO-YSZ films in an Ar-H2 gas flow environment, distinct characteristic peaks for cubic Ni and YSZ, without any observable NiO phase, were observed from the XRD results. In addition, SEM with energy-dispersive x-ray spectroscopy (EDS) showed that the Ni-YSZ film had increased porosity compared to that of the unreduced NiO-YSZ film.
Thesis (Master of Science in Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Thin films